Preliminary Outcomes of Distal IMAP and SEAP Flaps for the Treatment of Unstable Keloids Subject to Recurrent Inflammation and Infections in the Lower Sternal and Upper Abdominal Areas - Wang, Jue; Min, Peiru; Grassetti, Luca; Lazzeri, Davide; Zhang, Yi Xin; Nicoli, Fabio; Innocenti, Marco; Torresetti, Matteo; Levin, L. Scott; Persichetti, Paolo (Journal of Reconstructive Microsurgery, 2015)
Background We present the clinical application of the sixth internal mammary artery perforator (IMAP) and superior epigastric artery perforator (SEAP) flaps for the treatment of defects resulting from the excision of large lower sternal and upper abdominal keloids. Perforator selection and flap design were based solely on preoperative multidetector-row computed tomographic angiography (MDCTA) of the areas adjacent to the soft tissue defects.Methods Between January 2009 and June 2014, 15 patients with large, unstable keloids subject to recurrent inflammation and infections and with a history of multiple failed treatments underwent surgical excision and early postoperative radiation therapy. The defects were located in the upper abdomen (n = 6) or lower sternum (n = 9). All patients underwent preoperative MDCTA for perforator localization.Results A total of 15 patients underwent keloid removal followed by IMAP (n = 10) and SEAP (n = 6) flap coverage combined with early postoperative low-dose radiation therapy (350 cGy/5 fractions/5 days or 400 cGy/4 fractions/4 days). Flap sizes ranged from 9 × 5 to 17 × 6 cm. Only one IMAP flap developed a 2 × 2 cm tip necrosis, which was managed with dressing changes. The remaining flaps healed uneventfully with no keloid recurrence at 23.4 months. In all cases, the perforator location determined by preoperative MDCTA was precisely consistent with the intraoperative findings.Conclusion The sixth IMAP and SEAP flaps combined with early postoperative radiation therapy provided a valid and feasible approach for the surgical treatment of large keloids in the lower sternal and upper abdominal. MDCTA enabled detailed preoperative assessment of the perforators, facilitating both flap design and dissection, and saving operating time. Although longer follow-up is required, these preliminary results are encouraging.
Keywords: internal mammary artery perforator; superior epigastric artery perforator; keloid; pedicle propeller flap; computed tomographic angiography